Comparison of the Efficacy of Aspirin with Rivaroxaban in Postoperative DVT Prophylaxis after Hip Arthroplasty - Fahad Siddique Jato, Muzafar Hussain Buriro, Sajjad Ali, Muhammad Younis, Faheem Ahmed, Arshan Munir, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Patients suffering from severe hip arthritis and osteonecrosis are increasingly turning to total hip arthroplasty (THA) as a treatment option, according to recent research. If deep vein thrombosis (DVT) is not treated properly, it can result in a life-threatening pulmonary embolism as well as other potentially life-threatening consequences (PE). Aim: To compare the efficacy of aspirin with rivaroxaban in postoperative dvt prophylaxis after hip arthroplasty in patients at tertiary care hospital, Karachi Methodology: The College of Physicians and Surgeons of Pakistan approved this study prior to its completion. The Department of Orthopedics at JPMC, Karachi, chose those who had complete hip arthroplasty for the study. The school's ethical committee approved the study before it could begin. Before participating in the trial, all patients signed an informed consent form granting them permission to do so. Results: Patients from JPMC Karachi's Department of Orthopedics were included in the study. They were aged 49 to 75. Travel time to the hospital was an average of 58.878.19 years. They were aged 49 to 75. For every month, hour, and day spent in hospital, there are 14.416.14. Eighty people used aspirin, 32(40%) were 40-60 and 48(60%) were 61-75. In the rivaroxaban group, 40 patients (50%) were 40-60, and (61-75). The aspirin group had 80 patients, 38 male (47%) and 42 female (42%) (52.5%). One hundred and twenty-five patients (68.8%) were on rivaroxaban (31.2%). Conclusions: People who have a spontaneous venous thromboembolism should not be given long-term thromboprophylaxis after taking oral anticoagulants until more research is done. It is very important to figure out what DVY risk factors are in order to come up with preventative measures that are both safe and affordable. People can live longer if they get an early diagnosis and get treatment quickly, so they can live longer. High-quality, large-scale studies must be done before a conclusion can be drawn.